Comparative In Vitro Effects of Calcineurin Inhibitors on Functional Vascular Relaxations of Both Rat Thoracic and Abdominal Aorta - Ashok Jadhav; Venkat Gopalakrishnan; Ahmed Shoker (Advances in Pharmacological Sciences)
Background and Aim. Calcineurin inhibitors (CNIs) have shown to develop hypertension in transplant patients. The in vitro incubation effects of cyclosporine (CsA) and tacrolimus (Tac) on vascular relaxations of rat thoracic aorta (TA) and abdominal aorta (AA) need to be investigated. Methods. The optimal concentrations of CsA (1.0 mg/mL) and Tac (0.1 mg/mL) used to compare endothelium-dependent (acetylcholine (ACh)) and endothelium-independent (sodium nitroprusside (SNP)) vascular relaxation against the agonists in phenylephrine (PE-) constricted TA and AA of 13-week-old male Sprague Dawley rats (n=6). Results. In TA, the maximal vasodilator response elicited by ACh (control: Imax 98%) was significantly (P<0.01) inhibited by CsA (Imax 10%) but not by Tac (Imax 97%). In AA, (control: IC50 50 nM; Imax 100%) CsA (IC50 7 μM; (P<0.01) showed strong sensitivity to inhibit ACh-dependent vascular relaxation than Tac (IC50 215 nM (P<0.05); Imax 98%). CsA and Tac failed to affect the inhibitory responses to SNP in both TA and AA. Conclusion. CsA exerts profound inhibitory effect on endothelium-dependent vasodilatation as compared to Tac in both TA and AA. Aortic rings from the thoracic region are more sensitive to CNIs, since the vasodilator response to ACh is solely mediated by NO while in the AA, ACh likely recruits other endothelial mediators besides NO to maintain vasodilatation.